2019
DOI: 10.1038/s42004-019-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed Markovnikov hydrosilylation of terminal alkynes achieved by using a trimethylsilyl-protected trihydroxysilane

Abstract: Developing efficient strategies for Markovnikov hydrosilylation of alkynes is still an important goal. The steric and electronic properties of hydrosilanes are key factors in controlling selectivity in these reactions. Here by using a trimethylsilyl-protected trihydroxysilane, we report a mild, efficient strategy for Markovnikov hydrosilylation of terminal alkynes with the simple catalyst [Ir(μ-Cl)(cod)] 2 . A variety of terminal alkynes are hydrosilylated efficiently with outstanding α-regioselectivity. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…24 The most investigated application of complexes containing M-Si bonds to date is the (hydro)-silylation of unsaturated hydrocarbons; TM complexes have been shown to promote this chemistry for decades, and attention has turned to the f-block for comparative studies. [27][28][29][30] Also of signicance is the potential application of uranium silicides (e.g. U 3 Si 2 , USi 2 ) as alternatives to conventional UO 2 fuel due to an increase in uranium density and a larger thermal conductivity in the former materials, potentially allowing prolonged generation of energy from nuclear fuels.…”
Section: Introductionmentioning
confidence: 99%
“…24 The most investigated application of complexes containing M-Si bonds to date is the (hydro)-silylation of unsaturated hydrocarbons; TM complexes have been shown to promote this chemistry for decades, and attention has turned to the f-block for comparative studies. [27][28][29][30] Also of signicance is the potential application of uranium silicides (e.g. U 3 Si 2 , USi 2 ) as alternatives to conventional UO 2 fuel due to an increase in uranium density and a larger thermal conductivity in the former materials, potentially allowing prolonged generation of energy from nuclear fuels.…”
Section: Introductionmentioning
confidence: 99%
“…12 The substrate involving thioether group showed its specificity in affording hydrosilylation product. Encouraged by the promising applications of this type of structure and corresponding synthetic methods in manufacturing new interesting materials, as well as our findings that the interaction between a heteroatom (O, N, S) and iridium catalyst can effectively enhance diverse hydrosilylation processes, 13 here we showed our investigations on the thioether-facilitated hydrosilylation of steric 1,1-disubstituted alkenes under a simple iridium catalytic system (c, Scheme 1). A variety of substrates, including allylic and homoallylic sulfides, were hydrosilylated with high efficiency and selectivity.…”
Section: Introductionmentioning
confidence: 74%
“…1 H NMR control experiment showed this process completed within 2 hours, with observation of trace amount of by-products ( Supplementary Figure 1). Considering that both the steric effect of the hydrosilanes and the different electronic property of the Si-H bond of them might influence the hydrosilylation process, 13,14 we next examined the hydrosilane scopei. Decreased yields were obtained with the utilization of Ph2MeSiH, Ph3SiH, BnMe2SiH and Et3SiH (entries 8-11, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Ding's group realized the Markovnikov hydrosilylation of 1-alkynes under iridium catalysis by employing a TMS-protected trihydroxysilane (Scheme 30). 59 This protocol shows specific efficiency in the hydrosilylation of 1alkynes bearing various functional groups. Mechanistic studies revealed that the bulky hydrosilane was inactive in the presence of [(COD)IrCl] 2 , which allows chelation of the alkyne with the iridium center in the initial step.…”
Section: Scheme 29 Hydrosilylation Of Internal Thioalkynes Catalyzed mentioning
confidence: 98%